An assessment of study characteristics, quality and reporting in cancer prehabilitation literature: a scoping review - Caroline Dalton; Robert Copeland; Anna Myers; Samantha Welfare; Thomas Maden-Wilkinson; Liam John Humphreys (BMJ Open)
Background Cancer and its treatment can negatively impact physical function, general well-being and quality of life. An evidence-based strategy to manage this is to prescribe exercise. One approach is to prescribe exercise prehabilitation to improve pretreatment health and function. However, current exercise prehabilitation programmes are under-researched, and the quality of their reporting has not been systematically assessed.Objectives This review aimed to identify the following: the characteristics of prehabilitation exercise programmes; how intensity, physical function, patient-reported outcomes and treatment-related outcomes were measured; the quality of reporting and programme implementation.Eligibility criteria Studies were eligible for inclusion if they reported a cancer prehabilitation exercise intervention, reported outcomes relating to physical function and patient-reported outcomes, and full-text copies were available in English.Sources of evidence PubMed, Mednar and Scopus were screened for studies from inception until 4 of April 2024.Charting methods Exercise characteristics were extracted and manually charted in Microsoft Excel using the Template for Intervention Description and Replication. The tool for the assessment of study quality and reporting in exercise (TESTEX) framework was used to assess study quality and intervention reporting.Results 1495 results were retrieved, 28 of which were included. Exercise sessions lasted a mean of 42.5±21.9 min and were completed 3.7±1.3 times per week. 22 studies implemented concurrent exercise, five prescribed aerobic, and one prescribed resistance. High-intensity exercise was prescribed in four studies, moderate-high in 12, seven prescribed moderate, three prescribed low-moderate, and one was low intensity. 10 studies prescribed exercise intensity using the Borg Rating of Perceived Exertion Scale, five prescribed heart rate (HR) zones, six used a set workload, and seven did not monitor intensity. A mean TESTEX score of 9.3±2.3 out of 15 was achieved. The lowest scoring criterion (n=3) related to the reporting of the exercise dose. Conclusions There was heterogeneity among studies regarding exercise intervention characteristics and measures of effectiveness. The overall quality of reporting was satisfactory, yet inconsistencies were apparent regarding quantifying and monitoring exercise dose, which limits the ability of researchers and clinicians to replicate, evaluate or scale cancer prehabilitation exercise interventions, impeding evidence-based practice. As such, to be able to optimise cancer prehabilitation exercise programmes, research must first focus on improving the quality of reporting and standardising outcome measures and methods of monitoring and prescribing exercise.